Incoherent excitation of thermally equilibrated open quantum systems (2013)
Under natural conditions, excitation of biological molecules, which display nonunitary open system dynamics occurs via incoherent processes such as temperature changes or irradiation by sunlight or moonlight. The dynamics of such processes is explored analytically in a non-Markovian generic model Specifically, a system S in equilibrium with a thermal bath TB is subjected to an external incoherent perturbation BB (such as sunlight) or another thermal bath TB', which induces time evolution in (S + TB).Particular focus is on (i) the extent to which the resultant dynamics is coherent, and (ii) the role of "stationary coherences" established in the (S +TB) equilibration in response to the second incoherent perturbation. Results for systems with parameters analogous to those in light-harvesting molecules in photosynthesis show that the resultant dynamical behavior is incoherent beyond a very short response to the turn on of the perturbation.